Smarter Marketing Strategies for Boosting the Economy of Farmers and also GDP of Indian Economy - Vageesh, Revadigar; Balasubramanian, T; Majed Ahmed, Al-Mansoub; Amin Malik Shah, Abdul Majid
According to the report of the Union Ministry of the Cooperation of India the population of farmers and the manpower involved in the Agriculture and horticulture production and its business directly and indirectly is about 65%. And quite often much bigger farmers populations income suffers heavily because of following the same crop cultivation in the same regions of different parts of our country. And when they take it to local market for selling they end up in earning low price because of over production or else end up making a megre profit. Because of repetitive financial losses their confidence and also total well being gets affected severly and which affects our nations GDP severly. This can be effectively solved by educating our farmers by different convenient modes about scope of selling their crops and products domestically in India. For the traders involved in agribusiness about the export business with neighbouring countries, middle east and African countries. We also suggest about the absolute necessity of building infrastructure in APMC markets, and amending the necessary interstate and International policies for empowering the farmers of our great nation.